A atuação de uma Coordenadora Pedagógica na orquestração de intenções e ações de uma creche de São Paulo - Costi, Ricardo (2015)
The research aims to analyze the work and strategies of a Pedagogical Coordinator regarding the conduct of teachers' planning at a municipal day care center of São Paulo city located in a region under high economical and social vulnerability. It is understood planning as a possibility for realization of the objectives laid down in institutional documents and feature of the Pedagogical Coordination in the guidance and monitoring of teaching practice. The researched place is assessed as good by most parents or guardians, and is evidenced in the Regional Directorate of Education, by the educational projects it develops. It is a case study with participant observation, semi-structured interviews and documentary analysis of the Pedagogical Political Project of the day care center. Data analysis showed that the Pedagogical Coordinator orchestrates the teaching activities from structural conditions categorized as: a) founding or non-negotiable related to the principles and objectives of the Pedagogical Political Project; b) flexible or negotiable including the possibilities of listening to the group, the appreciation of autonomy; c) affective and professional constituting the qualified and committed support. The research has indicated that the Pedagogical Coordinator systematically questions the intentions of teaching practices having as parameter the principles, concepts and goals of early childhood education discussed in the Pedagogical Political Project of the day care. It appreciates, welcomes and enables qualifying ideas of attendance at the day care, proposing action strategies, protocols of conduct. It organizes spaces and materials promoting the teachers work in educational practice